The development of lulo creation dance to improve students’ social skills - Rahayu Pertiwi Sari; Siti Fatimahtun Zahra (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
This research aims to find out (1) the description of needs toward the model of Lulo dance of Southeast Sulawesi to improve students’ social skills and (2) utility, feasibility, and accuracy in the model of Lulo dance of Southeast Sulawesi to improve students’ social skills. This research applied the development research proposed by Borg & Gall. Small group testing was conducted to 12 students. Data collection technique used in this research was interview and social skill scale. This research employed descriptive statistic and qualitative descriptive analysis. The results point out that (1) students were indicated to have low social skills, so school counselors need social guidance and counseling services so that the video-based model of Lulo dance of Southeast Sulawesi was developed to improve students’ social skills (2) the validation test with 3 (three) experts shows that utility, feasibility, and accuracy in the model of Lulo dance of Southeast Sulawesi based on video were suitable to improve students’ social skills. The observation result from the limited group explained that the model of Lulo dance of Southeast Sulawesi could be accepted well by the students.